1994
DOI: 10.1002/bit.260440818
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dissolved oxygen tension on the synthesis of the antibiotic difficidin by bacillus subtilis

Abstract: The antibiotic, difficidin, and its hydroxylated derivative, oxydifficidin, were synthesized by cultures of Bacillus subtilis grown on a complex medium. Maximum titers of about 200 and 130 mg/L, respectively, were obtained. In fermentations where the dissolved oxygen tension (DOT) was controlled, the maximum specific growth rate was only reduced below 5% air saturation. DOT had little effect on the volumetric rate of synthesis of oxydifficidin but greatly influenced the rate for difficidin, which was reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…In each case the titers rose almost linearly over these 9 h periods allowing volumetric production rates to be calculated (Table 3). There was no significant trend in the volumetric production rates for oxydifficidin with the values (0.9-1.3 mg/lh) in the same range as reported for constant DOT fermentations [8]. However, it was clear that the volumetric difficidin production rate in the fermentation with cycling at 40% DOT increased with fermentation time up to 70 h. Whereas the difficidin production rates rose substantially between the initial constant DOT period and the subsequent cycling period for fermentations at 20 and 40% DOT there was only a small increase in the fermentation at 15% DOT indicating a deleterious effect of cycling about that DOT value.…”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…In each case the titers rose almost linearly over these 9 h periods allowing volumetric production rates to be calculated (Table 3). There was no significant trend in the volumetric production rates for oxydifficidin with the values (0.9-1.3 mg/lh) in the same range as reported for constant DOT fermentations [8]. However, it was clear that the volumetric difficidin production rate in the fermentation with cycling at 40% DOT increased with fermentation time up to 70 h. Whereas the difficidin production rates rose substantially between the initial constant DOT period and the subsequent cycling period for fermentations at 20 and 40% DOT there was only a small increase in the fermentation at 15% DOT indicating a deleterious effect of cycling about that DOT value.…”
Section: Resultssupporting
confidence: 68%
“…In a previous paper [8] we showed that the rate of difficidin synthesis was affected by the level of DOT and that a dramatic change was observed at approximately 20% air saturation. We have, therefore, carried out fermentations cycling the DOT (i) below this value, about 15% air saturation; (ii) at this critical value, about 20% air saturation and (iii) above this apparent critical value, about 40% air saturation.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations